The impact of an online support group on patients’ awareness of pregnancy-and lactation-induced osteoporosis - Sansin Tuzun; Eren Aygun (BMC Pregnancy and Childbirth)
Abstract Background Pregnancy and lactation-induced osteoporosis (PLO) is a serious and rare condition, which causes substantial physical and emotional distress. The rarity of PLO highlights the importance of alternative information sources such as online patient groups. This study aims to explore the experiences of PLO among members of a WhatsApp patient group and to analyze how participation in the group impacts members’ knowledge about their condition, psychological well-being, and healthcare decisions. Methods This cross-sectional study included forty-six members of the “Smile Please” WhatsApp patient group, diagnosed with PLO. A 9-item survey assessed membership duration, sources of group awareness, knowledge improvement, changes in fears and concerns, and impacts on treatment decisions. Data were collected through structured survey questions for quantitative analysis and an open-ended question to capture qualitative insights. Results The average age of participants was 33.8 ± 4.8 years, with a mean BMI of 23.2. Their group membership duration was 15.3 ± 16.8 months. Increased knowledge was reported by 46.3% regarding symptoms and diagnostic tools, 75.6% on treatment options, and 41.5% on side effects. Half the participants experienced decreased fear of the disease, and 41.9% reported reduced concerns about treatment side effects. The thematic analysis showed that participants received substantial emotional support from peers in the online support group, which alleviated feelings of isolation and provided motivation. They also gained insights into treatment options, especially medications, improving the decision-making process. Furthermore, they received practical coping strategies that fostered acceptance and positively impacted their overall well-being. Conclusions Online patient groups provide a unique platform where members can openly share their knowledge and experiences, thereby influencing their emotional well-being and healthcare decisions. These groups should be encouraged, especially for chronic and rare diseases like PLO.